2019
DOI: 10.1007/s11121-019-01000-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Bystander-Focused Interpersonal Violence Prevention Program with High School Students

Abstract: This study evaluated the effectiveness of a 7-session, bystander-focused, classroom delivered curriculum (i.e., Bringing in the Bystander-High School Curriculum [BITB-HSC]) in reducing rates of interpersonal violence among high school students. High schools (N = 26) were randomly assigned to the treatment or control condition. In classrooms in treatment schools, students (n = 1081) completed a baseline survey, participated in the BITB-HSC, and completed an immediate post-test, a short-term post-test (appx. 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 42 publications
(50 reference statements)
3
89
0
3
Order By: Relevance
“…Data were collected in the context of a larger cluster randomized control trial to evaluate a bystander‐focused violence prevention curriculum among high school students (Edwards, Banyard, Sessarego, Mitchell, & Chang, ). Baseline data collected before the implementation of the intervention were used for the current analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected in the context of a larger cluster randomized control trial to evaluate a bystander‐focused violence prevention curriculum among high school students (Edwards, Banyard, Sessarego, Mitchell, & Chang, ). Baseline data collected before the implementation of the intervention were used for the current analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Bystander roles have proven to be an effective source of primary, secondary and tertiary prevention. [18][19][20] This is also reflected by the fact that in one third of the cases of sexual violence, nobody reacted. Therefore, this subject should be addressed in the training and all university and hospital personnel should also receive a training in bystander roles.…”
Section: Discussionmentioning
confidence: 99%
“…These data are embedded in a larger project that evaluated via a cluster randomized control trial the BITB‐HSC among high school students during the 2014 to 2015 academic year (see Edwards, Banyard, et al, for student outcome data). In the larger study, high schools ( N = 25) were randomly assigned to the treatment ( n = 12) or control ( n = 13) condition; in the current paper, we use survey data from school personnel in the treatment condition ( N = 488) who completed a 4‐month follow‐up survey (at which time point exposure to intervention components was assessed since the intervention components were delivered between the baseline and 4‐month follow‐up survey).…”
Section: Methodsmentioning
confidence: 99%
“…Using a 26‐school cluster randomized control trial, researchers conducted an initial efficacy trial of the BITB‐HSC program. The results showed that students exposed to the BITB‐HSC demonstrated significant short‐term changes in rape myths, victim empathy, and bystander barriers, and long‐term changes in media literacy, bystander readiness, and knowledge relative to youth in the control conditions (Edwards, Banyard, et al, ). Although the BITB‐HSC had little long‐term impact on actual bystander behavior, there were reductions in sexual harassment and stalking among students in the intervention condition compared to the control condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation